Vibrational communication of subterranean rodents - Hrouzková, Ema (Jihočeská univerzita, 2012)
This PhD. thesis focuses on the vibrational communication of subterranean mammals, in particular, vocal communication of bathyergids (Heliophobius argenteocinereus, Fukomys mechowii, Fukomys darlingi) and seismic communication of Tachyoryctes. We recorded and analyzed the vocalization of three species and discussed the physical parameters of their vocalization in relationship to the special underground acoustic environment. Moreover, social systems of African mole-rats range from solitary to eusocial and thus our results enabled us to discuss the influence of sociality on vocal repertoire richness and its composition. Long distance communication possesses many challenges in underground environments; the only effective mean is seismic communication. We described for the first time seismic signaling in Tachyoryctes and proposed its function.
Vibrational communication of subterranean rodents
Keywords: Vocalization; seismic communication; Bathyergidae; Tachyoryctes; Vocalization; seismic communication; Bathyergidae; Tachyoryctes